The Reconstruction of Educational Basis in Homeschooling Group Khoiru Ummah - Purnama, Sigit (Nadwa: Jurnal Pendidikan Islam, 2019)
The growth of community-based schools such as homeschooling is a new trend in Indonesia. This model was introduced with more emphasis on the role of parents in education, islamic knowledge and thought as learning material. This article discusses the basic reconstruction of education, strategic applications, and learning techniques applied in the Homeschooling Khoiru Ummah Group (HSG KU). This is qualitative research with a descriptive-analytical approach. Data is collected through interviews, observation, and documentation. The results of the study show that in the HSG KU perspective, al-Ma'rifah is divided into two (1)al-'ilmu which have material as the object of research (al-maddah) obtained through the scientific method (thariqah ilmiyyah) and (2)tsaqofah which has materials as objects of research (al-maddah) and ideas (al-fikrah) are obtained through rational methods (tariqah aqliyyah). HSG KU implements talaqiyyan fikriyan (thoughts delivered through meetings) as learning strategies. While the technique (uslub) in learning is through dialogue, discussion, experimentation, and direct practice.